Advances in Modeling Agricultural Systems - Pardalos, Panos M.; Papajorgji, Petraq J. (Springer Optimization and Its Applications,, 2009)
This book presents an up-to-date review of advances in the mathematical modeling of agricultural systems. It covers a broad spectrum of problems and applications based on internet and communications technology, as well as methodological approaches based on the integration of different simulation and data management tools. Using real-world cases, each chapter presents a detailed solution of a problem in a particular field. This book demonstrates that regardless of the nature of the problem and the application domain, modeling is a central and important activity in the process of developing agricultural systems. Researchers and graduate students in the fields of agriculture and environmental studies will benefit from this book. It will also serve as an excellent reference for managers, team leaders, developers and modelers of agricultural and environmental systems and researchers in the applied computation field.